High prevalence of toxocara positive serology in a Peruvian pediatric hospital - Miranda Choque, Edwin (2014)
Introduction: Zoonotic diseases transmitted by domestic animals may be considered a public health problem in developing countries. Objective: To determine the frequency of positive toxocara serology in clinically suspected children. Design: Descriptive, cross-sectional study. Setting: Instituto Nacional de Salud del Niño (INSN), Lima, Peru. Participants: Children with positive toxocara serology. Methods: Clinical records of children with suspicion of toxocara infection during the period 2007-2010 were included. Main outcome measures: Frequency and characteristics of toxocara seropositive cases. Results: From the 242 cases studied 61.2% (148) were toxocara seropositive, with average age 6.8 (SD 3.8) years; the group 2-10 years-old represented 69.6% of the total; eosinophilia was the main reason for consultation in 70.9%. Conclusions: High frequency of toxocara positive serology is found at INSN in suspicious patients, especially in children 2-10 years-old with eosinophilia.